MEASUREMENT OF TENSION FORCES IN ROPES (Perner's Contacts, 2018)
This entry describe constructional design of a measurement device for detection tension forces in ropes. In the contribution, two principles of devices for setting the required value of tensile force in ropes are mentioned and subjected to the analysis of practical applicability.
Keywords: tension force, steel rope, electric lift, measurement device